The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3389/fendo.2018.00319
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Insufficient Sleep Has a Limited Impact on Circadian Rhythmicity of Subjective Hunger and Awakening Fasted Metabolic Hormones

Abstract: Weight gain and obesity have reached epidemic proportions in modern society. Insufficient sleep—which is also prevalent in modern society—and eating at inappropriate circadian times have been identified as risk factors for weight gain, yet the impact of chronic insufficient sleep on the circadian timing of subjective hunger and physiologic metabolic outcomes are not well understood. We investigated how chronic insufficient sleep impacts the circadian timing of subjective hunger and fasting metabolic hormones i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 67 publications
4
32
1
Order By: Relevance
“…We further found that circulating active ghrelin changed differently under circadian misalignment during wake (increase) versus sleep (decrease) periods. This can be attributed to the endogenous circadian rhythm of active ghrelin, for which the nadir (in the biological day) coincides with the sleep episodes of the circadian misalignment protocol and the peak (in the biological evening/night) coincides with the wake periods during circadian misalignment (33,34). Moreover, we found that the change in active ghrelin during misaligned wake periods was modulated by sex, with females as the major contributors to the overall increase.…”
Section: Discussionmentioning
confidence: 63%
“…We further found that circulating active ghrelin changed differently under circadian misalignment during wake (increase) versus sleep (decrease) periods. This can be attributed to the endogenous circadian rhythm of active ghrelin, for which the nadir (in the biological day) coincides with the sleep episodes of the circadian misalignment protocol and the peak (in the biological evening/night) coincides with the wake periods during circadian misalignment (33,34). Moreover, we found that the change in active ghrelin during misaligned wake periods was modulated by sex, with females as the major contributors to the overall increase.…”
Section: Discussionmentioning
confidence: 63%
“…A circadian rhythm was observed for hunger, whereby a trough in hunger was observed during the biological morning (0800) and a peak during the biological evening (2000). These hunger rhythms are stable and remained the same even upon changing meal timing (16) and under conditions of chronic insufficient sleep (86). These rhythms in hunger and appetite relate to the rhythms of the appetite hormone ghrelin.…”
Section: Circadian Systemmentioning
confidence: 88%
“…These rhythms in hunger and appetite relate to the rhythms of the appetite hormone ghrelin. Acylated ghrelin (the active form) has higher concentrations in the biological evening than in the biological morning, both in the fasted and postprandial states, consistent with hunger (86,87). The hunger peak at 2000 also coincides with the average timing of the last eating episodes in the United States at 2018, and the hunger trough at 0800 may also partly explain variability in breakfast preference (47).…”
Section: Circadian Systemmentioning
confidence: 92%
“…The effects of sleep curtailment with a long period or advanced wake time would be expected to differ from acute effects of sleep curtailment with delayed bed time. Previous study has reported that chronic sleep restriction does not alter subjective hunger levels and appetite hormones, but rather, they are more circadian-rhythm-dependent [30]. Olfactory responses seem to change based on circadian timing [31], which could also impact taste response.…”
Section: Discussionmentioning
confidence: 91%